Risk assessment of agriculture impact on the Frío River watershed and Caño Negro Ramsar wetland, Costa Rica - Fournier, María Luisa (2017)
The Caño Negro Ramsar wetland is a conservation area of great natural and societal value, located in the lower part of the Frío River watershed in the north of Costa Rica. Its aquatic ecosystems may be considered vulnerable to pollution due to recent changes in land use toward agriculture. In 2011 and 2012, quarterly sampling was done at ten sites located in the middle and lower sections of the Frío River Basin that pass through crop areas and later drain into Caño Negro wetland. Pesticide residues, nitrates, sediment concentrations, and diversity of benthic macroinvertebrates and fish biomarkers were studied in the selected sites. Additionally, risk of toxicity was calculated in two different ways: (1) by using a ratio of MEC to hazard concentrations threshold for 5% of species (HC5) to calculate a risk quotient (RQ), and (2) by using a ratio of MEC to available ecotoxicity data of native fish and cladocera for diazinon and ethoprophos, to obtain a risk quotient for native species (RQns). Results indicated that three out of the ten sites (rivers Thiales, Mónico, and Sabogal) showed variable levels of pollution including six different active ingredients (a.i.) of pesticide formulations (herbicides ametryn, bromacil, and diuron; insecticides cypermethrin, diazinon, and ethoprophos). Moreover, potential adverse effects on fishes in Thiales and Mónico rivers were indicated by cholinesterase (ChE) inhibition and glutathione S-transferase (GST) enhancement. Risk evaluations indicated pesticide residues of ametryn, bromacil, and ethoprophos to be exceeding the limits set by MTR, also RQ was high (>1) in 70% of the positive samples for diuron (most frequently found pesticide in water samples), cypermethrin, diazinon, and ethoprophos, and RQns was high for diazinon. Therefore, these substances might be of major concern for the ecological health of aquatic ecosystems in the middle basin of the Frío River. The most critical site was Mónico River, which had the highest pollution (75% detection samples with 3–5 a.i.) and highest calculated risk (RQ > 1 in 75% of the samples). This is also the river that most directly drains into the protected wetland. Even though pesticide pollution in this area is not as severe as in other parts of Costa Rica, it is imperative that measures are taken, particularly in the surroundings of Mónico River, in order to diminish and mitigate possible detrimental effects to biota in Caño Negro Ramsar Site.